Cigarette smoking and alcohol-related liver disease - Hui-Min Lin; Jing-Rong Zhang; Meng-Xue Li; Hui Hou; Hua Wang; Yan Huang (Liver Research)
China is a major consumer of alcohol and tobacco. Tobacco and alcohol use are closely linked, with up to 90% of alcoholics having a history of tobacco use, and heavy smokers also tending to be alcoholics. Alcohol-related liver disease (ALD), one of the most common and serious complications of chronic alcohol intake, involving hepatic steatosis, hepatitis, hepatic fibrosis, cirrhosis and hepatocellular carcinoma (HCC), has become one of the globally prevalent chronic diseases. An increasing number of studies have focused on the association between smoking and ALD and explored the mechanisms involved. Clinical evidence suggests that smoking has a negative impact on the incidence and severity of fatty liver disease, progression of liver fibrosis, development of HCC, prognosis of patients with advanced liver disease, and alcohol-related liver transplant recipients. The underlying mechanisms are complex and involve different pathophysiological pathways, including free radical exposure, endoplasmic reticulum stress, insulin resistance, and oncogenic signaling. This review discusses the deleterious effects of smoking on ALD patients and the possible underlying mechanisms at several levels. It emphasizes the importance of discouraging smoking among ALD patients. Finally, the pathogenic role of electronic cigarettes, which have emerged in recent years, is discussed, calling for an emphasis on social missions for young people.